Development and performance comparison of MPI and Fortran Coarrays within an atmospheric research model - Rasmussen, Soren; Gutmann, Ethan D.; Friesen, Brian; Rouson, Damian; Filippone, Salvatore; Moulitsas, Irene (IEEE, 2018)
A mini-application of The Intermediate Complexity Research (ICAR) Model offers an opportunity to compare the costs and performance of the Message Passing Interface (MPI) versus coarray Fortran, two methods of communication across processes. The application requires repeated communication of halo regions, which is performed with either MPI or coarrays. The MPI communication is done using non-blocking two-sided communication, while the coarray library is implemented using a one-sided MPI or OpenSHMEM communication backend. We examine the development cost in addition to strong and weak scalability analysis to understand the performance costs.